Comparison of Small Intestinal Submucosal Graft and Autologous Tissue in Prevention of CSF leak after Posterior Fossa Craniotomy - Totten, Douglas J.; Manzoor, Nauman F.; Yancey, Kristen L.; Yawn, Robert J.; Haynes, David S.; Rivas, Alejandro (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective To compare the use of porcine small intestinal submucosal grafts (SISG) and standard autologous material (fascia) in prevention of cerebrospinal fluid (CSF) leak and pseudomeningocele formation after translabyrinthine resection.Setting Set at the tertiary skull base center.Methods This is a retrospective chart review. After Institutional Review Board approval, we performed a retrospective cohort study evaluating CSF leak in patients who underwent resection of lateral skull base defects with multilayered reconstruction using either fascia autograft or porcine SISGs. Demographics were summarized with descriptive statistics. Logistic regression was used to compare autograft and xenograft cohorts in terms of CSF complications.Results Seventy-seven patients underwent lateral skull base resection, followed by reconstruction of the posterior cranial fossa. Of these patients, 21 (27.3%) underwent multilayer repair using SISG xenograft. There were no significant differences in leak-associated complications between autograft and xenograft cohorts. Ventriculoperitoneal shunt was necessary in one (1.8%) autograft and one (4.8) xenograft cases (p = 0.49). Operative repair to revise surgical defect was necessary in three (5.4%) autograft cases and none in xenograft cases.Conclusion The use of SISG as a component of complex skull base reconstruction after translabyrinthine tumor resection may help reduce CSF leak rates and need for further intervention.
Keywords: submucosal graft; xenograft; cerebrospinal fluid leak; craniotomy